The Effect of Using Electronic Dictionary in Learning English Language by Libyan Students (A Case Study of the Students of English Department at Education Faculty-Waddan of Al-Jufra University) (Journal of Human Sciences, 2023)
Electronic dictionaries have revolutionized the educational landscape, providing instantaneous access to a wealth of lexical knowledge for students and educators alike. This study aimed to find out the effect of using an Electronic Dictionary in learning English Language by Libyan Students: The English department at the Education Faculty of Al-Jufra University. This study applied descriptive qualitative method. The data in this study were obtained through a document analysis (questionnaire). Thirty-five students of English department participated in the questionnaire that was used in this study. The results of this study report that all students depend on the electronic dictionaries in their studies, but they face some difficulties in using it as a machine. Most students use the multi-language dictionary to get the meaning of the word in Arabic. Even though, more than 50% percent of the students find all words that they need in the e-dictionary. Most students face difficulties in selecting the suitable meaning of the word in the context. Moreover, about 50% of the students face difficulty in finding explanations for grammar tasks in E-dictionaries that they use. They face difficulty in using dictionaries that use English language only. That means they depend on their native language for learning English language.  Transitivity of the meaning of the word confuses them in selecting the suitable meaning, some words don’t exist in the dictionary, in the translation of phrasal verbs, a translation of abbreviations and some words don’t have any translation in Arabic language. On the other hand, electronic dictionary helps them to improve their English vocabularies.